Developing Ecological Awareness (Adab Al-Bī’ah) Among Madrasah Ibtidaiyah Students Through Natural Realia-Based Experiential Learning - Kholidatul Fauziyah; Reza Regar; Ansori Ansori (Jurnal Wahana Literasi Pendidikan, 2026)
This study is motivated by the importance of strengthening students' environmental character amid increasing ecological problems that have not been balanced by concrete behavioral awareness. This study aims to analyze the internalization process of environmental ethics (adab al-bī’ah) among Adiwiyata-based madrasah students through an experiential learning model utilizing natural realia media. A qualitative descriptive approach with a retrospective case study design was employed at MIN 3 Bondowoso. Data were gathered reconstructively post-learning activities through in-depth interviews with the fifth-grade homeroom teacher, students, and parents, and were validated through post-learning daily observations and documentation. Data trustworthiness was ensured using source triangulation. The findings indicate that the experiential learning model utilizing natural realia media successfully develops students' ecological awareness holistically. The internalization of adab al-bī’ah is consistently mapped through students' reflective memories, forming three active dimensions of post-activity behavior: hifzh al-bī'ah (preserving school environmental sustainability), ihsān ilā al-hayawān (developing active empathy toward animals), and daily self-regulation. The synergy between the reflection of realia-based learning and the Adiwiyata school culture is proven to accelerate the transformation of theoretical ecological knowledge into consistent pro-environmental behavior that extends to the students' home environments.